Humoral Inflammatory Markers of Total Immunoglobulin E (IgE) Exposure on Palm Oil Plantation Pesticide Sprayers - Awantari, Aprillia; Susilowati, Indah Tri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Pesticides are often used in oil palm plantations to prevent disturbing animals and plants. Pesticide sprayers are vulnerable to pesticide exposure which can reduce cholinesterase levels is an indicator of pesticide poisoning. Long-term pesticide exposure and excessive doses cause the production of free radicals in the body, thereby increasing inflammatory markers, one of which is total IgE. This study aimed to describe cholinesterase and total IgE levels in oil palm farmers. This study used the quantitative-descriptive research method. The sampling was conducted at PT. X in Sanggau District of West Kalimantan Province. Examining cholinesterase levels used the Architec c-8000 device with the DGKC butyrylthiocholine 37°C method, while total IgE used the immunochemmiluminescent method with the Immulite 2000 device. The examination was carried out at the Prodia National Reference Lab in Jakarta. Based on the cholinesterase measurement results taken from 133 workers who underwent medical check-ups, 20 data were taken that were close to the threshold value less than normal to examine total IgE levels. The results obtained from the overview of cholinesterase levels showed that 20 pesticide sprayers (100%) had normal cholinesterase levels, and four (20%) had normal total IgE levels. Pesticide exposure will decrease cholinesterase levels, and increase IgE levels.